Understanding readiness for building a decentralised data hub for agricultural data in Guatemala - Stiglich, Lucas; Snaith, Ben; D'Addario, Josh (2024)
This report examines the feasibility of implementing a decentralized data-sharing hub for agricultural stakeholders in Guatemala, supporting the United Nations Sustainable Development Goals (SDGs) for food security, nutrition, and sustainable agriculture. The proposed hub aims to facilitate data-driven decision-making across descriptive, prescriptive, predictive, and proactive levels by enabling streamlined sharing of agro-climatic, agricultural, and socio-economic data. Through analysis of open user-centric data sharing models and legal-regulatory barriers, this study investigates the opportunities and challenges in developing such a decentralized architecture. The findings presented by the Open Data Institute (ODI) provide insights into establishing a robust agricultural data ecosystem that can drive transformative progress in Guatemala's agricultural sector.